STUDI AWAL PEMBUATAN PUPUK KCL BERBAHAN DASAR SABUT KELAPA (Cocos nucifera) PADA TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Dian Nirwana Harahap (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
This research told about making KCl Fertilizer base coconut waste and applied to the cayenne pepper plant (Capsicum frutescens L.). Two samples used as initial experiments. The purpose of this study was to determine the initial growth of the cayenne plant (Capsicum frutescens L.) when treated with the addition of KCl fertilizer. The method used is to inculcated cayenne pepper plant seeds for three weeks and transferred in small polybags with the same soil nutrient state. Samples C0 (without KCl Fertilizer) and C1 (KCl Fertilizer Treatment). Plants are observed every week for two months. The results showed that C1 plants grew faster than C0.